PLA/PHB-Based Materials Fully Biodegradable under Both Industrial and Home-Composting Conditions - Fogašová, Mária; Figalla, Silvestr; Danišová, Lucia; Medlenová, Elena; Hlaváčiková, Slávka; Vanovčanová, Zuzana; Omaníková, Leona; Baco, Andrej; Horváth, Vojtech; Mikolajová, Mária; Feranc, Jozef; Bočkaj, Ján; et al. (Polymers, 2022)
In order to make bioplastics accessible for a wider spectrum of applications, ready-to-use plastic material formulations should be available with tailored properties. Ideally, these kinds of materials should also be "home-compostable" to simplify their organic recycling. Therefore, materials based on PLA (polylactid acid) and PHB (polyhydroxybutyrate) blends are presented which contain suitable additives, and some of them contain also thermoplastic starch as a filler, which decreases the price of the final compound. They are intended for various applications, as documented by products made out of them. The produced materials are fully biodegradable under industrial composting conditions. Surprisingly, some of the materials, even those which contain more PLA than PHB, are also fully biodegradable under home-composting conditions within a period of about six months. Experiments made under laboratory conditions were supported with data obtained from a kitchen waste pilot composter and from municipal composting plant experiments. Material properties, environmental conditions, and microbiology data were recorded during some of these experiments to document the biodegradation process and changes on the surface and inside the materials on a molecular level.
Keywords: home-compost; biodegradation; polyhydroxybutyrate (PHB); polylactic acid (PLA); industrial compost; blend polymeric material